2013
DOI: 10.1371/journal.pone.0081412
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glucose Transporters in Aspergillus nidulans

Abstract: To characterize the mechanisms involved in glucose transport, in the filamentous fungus Aspergillus nidulans, we have identified four glucose transporter encoding genes hxtB-E. We evaluated the ability of hxtB-E to functionally complement the Saccharomyces cerevisiae EBY.VW4000 strain that is unable to grow on glucose, fructose, mannose or galactose as single carbon source. In S. cerevisiae HxtB-E were targeted to the plasma membrane. The expression of HxtB, HxtC and HxtE was able to restore growth on glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 65 publications
1
47
3
Order By: Relevance
“…Under temperature induced oxidative stress, fungi reduce the glucose and ammonia uptake (Li et al 2008). In this way, the low temperature-induced stress can cause a dynamic rearrangement of the metabolic flux to the pentose phosphate pathway leading to the generation of the reduced electron carrier NADPH (Dos Reis et al 2013). Fungal cells accelerated the production of glucose by gluconeogenesis and the production of amino acids important to compose the repertoire of molecules to the oxidative stress response (Dos Reis et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Under temperature induced oxidative stress, fungi reduce the glucose and ammonia uptake (Li et al 2008). In this way, the low temperature-induced stress can cause a dynamic rearrangement of the metabolic flux to the pentose phosphate pathway leading to the generation of the reduced electron carrier NADPH (Dos Reis et al 2013). Fungal cells accelerated the production of glucose by gluconeogenesis and the production of amino acids important to compose the repertoire of molecules to the oxidative stress response (Dos Reis et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This fact, plus additional insights observed at genomic, transcriptomic and proteomic level gave strong indications that RhtA acts as a specific transporter for L-rhamnose, but did not provide direct evidence. To assay transport capacity and quantify uptake kinetics, radiolabeled sugar uptake experiments can be performed with the mentioned yeast strain (Colabardini et al, 2014;dos Reis et al, 2013;Leandro et al, 2013;Sloothaak et al, 2015;Subtil and Boles, 2011;Wahl et al, 2010). This approach was followed in the present study as a final step to prove the ability of RhtA to transport L-rhamnose.…”
Section: Discussionmentioning
confidence: 99%
“…MstA also showed a preference for glucose, while being able to transport other monosaccharides as well (Vankuyk PA et al, 2004). Similarly, substrate specificity of Aspergillus nidulans hexose transporters HxtB and HxtC has been assayed (dos Reis et al, 2013), and a reduction of glucose uptake of 70 to 80 % was observed for galactose, fructose and mannose. In accordance to the functioning of many glucose transporters from other filamentous fungi, the function of MstG and…”
Section: Mstg and Msthmentioning
confidence: 99%
See 2 more Smart Citations